The Impact of Academic Optimism on Elementary English Language Arts Achievement in Rural Missouri Schools - White, Jill Flakne (Southwest Baptist University, 2016)
This study researched the difference in achievement of students on annual Missouri fourth grade English language arts assessment in schools with high academic optimism versus achievement of students in schools with low academic optimism. The study also examined the impact of poverty level combined with academic optimism on student achievement. The study extends the work of Hoy, Tarter, and Woolfolk Hoy (2006) to 50 rural elementary schools in Missouri. Teachers were surveyed using the School Academic Optimism Scale. Although results of this study failed to show any significant difference in school achievement based on levels of academic optimism, the outcomes showed academic optimism had potential to impact student achievement. It is reasonable to conclude that positive impact on student achievement could be found in a larger sample of similar schools. Understanding how the components of academic optimism work together could be beneficial to schools looking to improve student achievement.